Sciurus alleni and Otospermophilus variegatus winter activity in Nuevo León, México - Mercado-Morales, David (Therya Notes, 2022)
Water and food availability during winter is essential for the survival of non-hibernating squirrels in temperate forests; tree and ground squirrels have different survival strategies during winter. This note reviews the winter activity and behavior of Sciurus alleni and Otospermophilus variegatus at ground level. Using camera traps, in a water spring and in a natural wildlife crossing, within a walnut forest (Juglans mollis), the activity and behavior of both squirrels was recorded; furthermore, by direct observation, the search, storage and dispersion of nuts was analyzed. The winter activity pattern of S. alleni is long bimodal in both sites and for O. variegatus it depends on the habitat of the site ranging from short unimodal to multimodal. Sciurus alleni stores nuts on a scattered pattern. The type of behavior is situational depending on the site of observation, drinking water at the water spring, and travelling at the wildlife crossing. The presence of a chipmunk Neotamias solivagus was also recorded confirming its activity during winter. Sciurus alleni is active during the whole winter even on sub-zero temperatures and at twilight, differing from O. variegatus which displayed short periods of activity, showing that both squirrels have different strategies to avoid overlapping their niche. The results of this study revealed the importance of water sources and walnut trees for the survival of S. alleni and O. variegatus in the cold and dry winter season in the forests of Cumbres de Monterrey National Park.